A comprehensive project for the research and conservation of sloths in cacao plantations in Costa Rica - Vaughan, Christopher (2022)
The two-toed sloth (Choloepus hoffmanni) and the three-toed sloth (Bradypus variegatus), today considered Costa Rican national symbols, were studied for 13 years (2004-2016) in and around a cacao farm in the project “Theobroma cacao: Biodiversity in Total and Partial Forest Canopies”. This interinstitutional and interdisciplinary sloth research carried out by six departments in five institutions covered the following areas: a) spatial ecology, b) behavior, c) wildlife health, d) demography, e) genetics, and f) conservation. Twenty-six (26) scientific publications resulted, most with new information about sloths; some are summarized in this article. Sloth conservation depends on a variety of components, including: i) protection and regeneration of habitat where they live and transit, especially cacao plantations, riparian forests, live fences, and trees in pastures, ii) environmental education programs, iii) avoid extracting and selling sloths to rescue centers and private zoos, and iv) continue research and monitoring programs.